Resilience and Vulnerability: The Haouz Earthquake's Effect on Housing In The Western High Atlas of Morocco - Ait Zamzami, Hamza; Elaanzouli, Mohammed; Saidi, Jamila; Boumeaza , Taieb (International Journal for Disaster and Development Interface, 2024)
This article delves into the vulnerability of traditional dwellings and cluster housing in the Western High Atlas region of Morocco, highlighting the major challenges they face during earthquakes. These houses, often built with natural materials such as earth, stone and wood, reveal structural limitations in the face of nature's relentless forces. More specifically, the article looks at the devastating Al Haouz earthquake of 2023, which marked the region's history as the most powerful earthquake in over a century. It left behind a tragic legacy of loss of life and considerable material damage. This underlines the imperative of understanding the seismic risks to which these traditional dwellings are exposed, particularly in a culturally and geologically rich and tectonically active region. The article goes beyond simply identifying the problems, highlighting the considerable efforts made by the government and civil society to rebuild and prepare the region for similar disasters in the future. It also highlights the need to strengthen the resilience of these traditional dwellings and to reconsider building standards to better cope with seismic risks.